Taxation and the Allocation of Talent - Lockwood, Benjamin B.; Nathanson, Charles G.; Weyl, E. Glen (Social Science Research Network, 2014)
Income taxation affects the allocation of talent by blunting the material incentives to enter high-paying professions. If, as the literature suggests, the ratio of social to private product is lower in high-paying professions (e.g., finance and law) than in low-paying professions (e.g., teaching and scientific research), progressive taxation is justified even absent a redistributive motive. Optimal taxes are highly sensitive to the size of externalities, which are currently poorly measured. Under our baseline calibration drawn from the literature, the Reagan tax reforms account for a fifth of the increase in pre-tax top income shares and reduce output.